2008
DOI: 10.1152/ajpendo.00560.2007
|View full text |Cite
|
Sign up to set email alerts
|

Development of hyperinsulinemia and insulin resistance during the early stage of weight gain

Abstract: -Obesity is associated with insulin resistance and hyperinsulinemia, which is considered to be a core component in the pathophysiology of obesity-related comorbidities. As yet it is unknown whether insulin resistance and hyperinsulinemia already develop during weight gain within the normal range. In 10 healthy male subjects the effect of intentional weight gain by 2 BMI points was examined on insulin. C-peptide and glucose levels following a meal, 75 g of glucose, and a two-step hyperglycemic clamp increased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
76
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 42 publications
9
76
0
4
Order By: Relevance
“…This is consistent with previous studies of short-term (3-days) [15] and long-term 272 (4.5-months) overfeeding [32] in healthy lean men. Our initial hypothesis was that FH+ 273 would have greater metabolic defects associated with overfeeding.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous studies of short-term (3-days) [15] and long-term 272 (4.5-months) overfeeding [32] in healthy lean men. Our initial hypothesis was that FH+ 273 would have greater metabolic defects associated with overfeeding.…”
supporting
confidence: 93%
“…Consistently, in response to 5-days overfeeding, healthy lean 280 men increased insulin secretion during IVGTT [12]. In longer term overfeeding studies, 281 reduced insulin clearance was observed after 4.5-months and significant weight gain in lean 282 young men [32]. These findings are similar to those in moderately fat fed dogs, where an 283 initial increase in beta cell secretion is observed at 6-weeks, which is no longer evident at 3-284 months when hyperinsulinemia is maintained via reduced insulin clearance by the liver [33].…”
mentioning
confidence: 83%
“…Likewise, previous studies have found a consistent decrease in IS in response to short-term OF (X7 days) in healthy lean subjects, as assessed by hyperinsulinemic euglycemic clamp, 14,15 and by oral or intravenous glucose tolerance test. 14,16 In these studies, including OF up to 14 days, mean weight change varied between 0.3 and 3.0 kg, 12,15,16 which is similar to the 1.6 kg weight gain in our subjects (Figure 1b). The observed decrease in IS with OF might be due to metabolic effects of increased energy and macronutrient intake per se, as well as to alterations in body composition (i.e., an accumulation of ectopic fat).…”
Section: Discussionsupporting
confidence: 72%
“…In lean men, clamp-derived IS remained unchanged following 3 days OF at þ 50% energy, 13 whereas an increase in body mass index by two units has been shown to impair IS in the fasting state, in response to oral and intravenous glucose load, as well as during an euglycemic glucose clamp protocol. 14 A more recent study on lean men has shown that 5 days of high-fat OF at þ 50% energy needs induced a decline in hepatic IS as assessed by clamp, which was compensated by increased insulin secretion. 12 As insulin secretion may compensate for changes in IS in healthy individuals, it is crucial to examine IS in relation to insulin secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Although insulin secretion has been extensively studied (Mayhew et al 1969, Meglasson & Matschinsky 1986, Prentki et al 2013, less attention has been paid to insulin clearance. However, this process seems to be as important (or even more) as insulin secretion in the establishment of hyperinsulinemia in obese patients (Erdmann et al 2008(Erdmann et al , 2009). …”
Section: Introductionmentioning
confidence: 99%